(untitled) (Al-Academy, 2019)
The current research studies the aesthetic framework for the dialectical development of the functions of the contemporary theater director in an aesthetic approach to the mechanisms of functional overlap between the dramaturgy and direction functions, and scenography and direction, the detection of the controversial structure of that overlap, and what can be summed up in the following question: (what are the aesthetic approaches of the dialectical development in the function of the contemporary theatre director?). The research is determined by a pivotal aim which is (knowing the aesthetic nature of the dialectical development in the functions of the contemporary theater director). The researcher addressed his research in three frameworks: the methodological framework in which the researcher identified the research problem, importance, goal, and limits, then the theoretical framework, which consists of two dimensions: the first dealt with a historical overview of the origins and methods of direction , and the second dimension dealt with the theme of direction dialectics: dialectic of the dramaturgy director, and the scenography director , ending with a set of theoretical indicators. The procedural framework included the researcher’s procedures of dropping the indicators, which he concluded from his theoretical framework, on his research sample which he identified as a model for the study. The research concluded with a number of conclusions, the most important of which are:1- The data of contemporary dramaturgy formed an advanced function for the contemporary director, and a directing task to manage the aesthetic awareness according to the direction vision.2- The data of contemporary scenography practice formed one of the advanced functions of the contemporary director, and a directing task through the design of sensory cognitive plans of the scene.